Up-Regulation of miR-9 Target CBX7 to Regulate Invasion Ability of Bladder Transitional Cell Carcinoma - Xie, Dalong (Med Sci Monit, 2015)
BACKGROUND: Bladder urothelial carcinoma is the most common genitourinary system cancer in China. The objective of this study was to investigate whether the miR-9 can regulate the invasion ability of human bladder transitional cell carcinoma cells by down-regulation of CBX7. MATERIAL/METHODS: The expression of miR-9 was detected by quantitative real-time PCR in bladder transitional cell carcinomas (TCC) and normal bladder transitional cell (NBTC) samples. Bioinformatics software was used to predict some potential target genes of miR-9. T24 cells were transfected with pre-miR-9, and the CBX7 protein expression was detected by Western blot. Luciferase activities assay was selected to verify that CBX7 was a direct and specific gene of miR-9. T24 cells were transfected with pcDNA-CBX7, and the expression of CBX7 gene was detected. Then, the transwell assay was used to detect the invasion ability of T24 cells with CBX7 over-expression. RESULTS: The expression of miR-9 increased significantly in human TCC specimens compared to that in NBTC specimens. TargetScan and PicTar software programs predicted CBX7 gene was a target gene of miR-9. The pre-miR-9 could up-regulate the miR-9 expression and down-regulate CBX7 protein expression. The luciferase activities assay verified that CBX7 gene was a direct and specific target gene of miR-9. The pcDNA-CBX7 transfection could up-regulate the CBX7 protein expression, and the invasion ability of T24 cells with CBX7 over-expression decreased significantly. CONCLUSIONS: Aberrantly expressed miR-9 contributes to T24 cells invasion, partly through directly down-regulating CBX7 protein expression in TCC. This miRNA signature offers a new potential therapeutic target for TCC.